1976
DOI: 10.1029/ja081i025p04715
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric neutrons

Abstract: Additional calibrations of the University of California double‐scatter neutron detector and additional analysis corrections lead to the slightly changed neutron fluxes reported here. The theoretical angular distributions of Merker (1975) are in general agreement with our experimental fluxes but do not give the peaks for vertical upward and downward moving neutrons. The theoretical neutron escape current J2π (Merker, 1972; Armstrong et al., 1973) is in agreement with the experimental values from 10 to 100 MeV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…The background signal is mainly caused by galactic cosmic ray particles interacting with the space craft and producing low-energy neutrons. As an estimate of the induced background neutron flux in a thick low-Z target we used the isotropized atmospheric albedo spectrum from Preszler et al, 1976. Assuming an instrumental angular resolution (1r) of 5°and a mean neutron scatter angle of 45°the acceptance solid angle for background events is 0.77 sr. By folding the neutron spectrum with the double scatter efficiency (Fig. 5(a)) we get a conservative number of background counts above 10 MeV of 0.05 s À1 , i.e., $100 integrated over the event.…”
Section: Sensitivitymentioning
confidence: 99%
“…The background signal is mainly caused by galactic cosmic ray particles interacting with the space craft and producing low-energy neutrons. As an estimate of the induced background neutron flux in a thick low-Z target we used the isotropized atmospheric albedo spectrum from Preszler et al, 1976. Assuming an instrumental angular resolution (1r) of 5°and a mean neutron scatter angle of 45°the acceptance solid angle for background events is 0.77 sr. By folding the neutron spectrum with the double scatter efficiency (Fig. 5(a)) we get a conservative number of background counts above 10 MeV of 0.05 s À1 , i.e., $100 integrated over the event.…”
Section: Sensitivitymentioning
confidence: 99%
“…These atmospheric neutrons are produced by the interactions of cosmic ray protons, alpha particles, and their secondaries with nitrogen and oxygen nuclei in the Earth's atmosphere. The neutron fluxes from about 5 to 200 MeV were measured at 41 ø north geomagnetic latitude (NGML) by Preszler et al [1972Preszler et al [ , 1974Preszler et al [ , 1976, Kanbach et al [1974], and Lockwood et al [1976Lockwood et al [ , 1979. A review of the early theory and measurements [White, 1973] also includes results at 46 ø and 71 ø NGML measured by Sirnnett et al [1972].…”
Section: Introductionmentioning
confidence: 99%
“…A number of tests of the theories [Merker, 1972[Merker, , 1975Armstrong et al, 1973] for the production of neutrons by cosmic ray interactions in the atmosphere, using energy, angle, altitude, and latitude distributions, were carried out on balloon flights at a few grams per square centimeter residual atmosphere [Preszler et al, 1974[Preszler et al, , 1976Kanbach et al, 1974;Lockwood et al, 1976Lockwood et al, , 1979Bhatt, 1983Bhatt, , 1986. While the experimental data and theoretical calculations were not always as detailed or significant as desired, the major results were in reasonable agreement, and the production of neutrons was mostly understood.…”
Section: Introductionmentioning
confidence: 99%
“…At E• > 70 MeV there is disagreement between calculated and measured neutron angular distributions[Merker, 1975;Kanbach et al, 1974], but this does not affect the results reported here. In converting •.,•uP at 0 g/cm •' to a neutron leakage current we used the measured neutron angular distributions 30 < E, < 75 MeV these rates are lower than those measured byPreszler et al [1976] and those calculated byArmstrong et al [1973] andMerker [1972].…”
mentioning
confidence: 99%